The effectiveness of cooperative learning on writing skills for 9th graders at Binh Phu secondary school - Le, Thuy Hanh Thao (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study examines the effectiveness of cooperative learning on the writing skills of ninth-grade students at Binh Phu Secondary School and investigates their attitudes and perceptions of cooperative learning. A case study research design was employed, integrating both quantitative and qualitative data collection methods. The research instruments included documents and interviews. The analysis in this study is based on the time series method proposed by Yin [1]. The findings revealed that cooperative learning significantly enhanced students’ writing skills in terms of organization, content, and language use. The students’ writing improvement was observed over a three-week period. In the individual error check, students identified a total of 102 errors. However, in the group error check, 331 errors were identified, and 290 out of 331 errors were successfully corrected. Additionally, students expressed positive personal views on cooperative learning with 93% of students supported cooperative learning and 7% of students found cooperative learning was ineffective.